2023
DOI: 10.3389/fevo.2023.703946
|View full text |Cite
|
Sign up to set email alerts
|

Predicting near-term, out-of-sample fish passage, guidance, and movement across diverse river environments by cognitively relating momentary behavioral decisions to multiscale memories of past hydrodynamic experiences

R. Andrew Goodwin,
Yong G. Lai,
David E. Taflin
et al.

Abstract: Predicting the behavior of individuals acting under their own motivation is a challenge shared across multiple scientific fields, from economic to ecological systems. In rivers, fish frequently change their orientation even when stimuli are unchanged, which makes understanding and predicting their movement in time-varying environments near built infrastructure particularly challenging. Cognition is central to fish movement, and our lack of understanding is costly in terms of time and resources needed to design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 494 publications
0
4
0
Order By: Relevance
“…Nevertheless, the larger steelhead smolts in this study may have been better able to respond actively to changing conditions than the smaller salmon smolts in the study by Holleman et al (2022; average fork length of smolts: 77 mm [their study] versus 245 mm [present study]). Goodwin et al (2023) also observed a range of behaviors among Chinook Salmon smolts at the diffluence of Georgiana Slough from the Sacramento River. Using a fish cognition model, they demonstrated that fish movement in the junction depends not only on current hydrodynamic conditions, but also on flow conditions and fish behavior from the recent past (i.e., memory).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Nevertheless, the larger steelhead smolts in this study may have been better able to respond actively to changing conditions than the smaller salmon smolts in the study by Holleman et al (2022; average fork length of smolts: 77 mm [their study] versus 245 mm [present study]). Goodwin et al (2023) also observed a range of behaviors among Chinook Salmon smolts at the diffluence of Georgiana Slough from the Sacramento River. Using a fish cognition model, they demonstrated that fish movement in the junction depends not only on current hydrodynamic conditions, but also on flow conditions and fish behavior from the recent past (i.e., memory).…”
Section: Discussionmentioning
confidence: 82%
“…As an alternative to depicting fish as drifting particles, several researchers have observed active swimming behavior by salmonid smolts at river junctions in this system and elsewhere (Holleman et al 2022;Goodwin et al 2023). Holleman et al (2022) performed twodimensional tracking of acoustic-tagged spring Chinook Salmon smolts at the head of Old River and observed a variety of behaviors, including both positive and negative rheotaxis and lateral movement from one side of the channel to the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other CFD solutions, such as Large-eddy Simulation (LES), permit solution of instantaneous flow fields that contains hydraulic structures (e.g., eddies) with more transient characteristics that may influence different leaping behaviors over time. However, there are currently no methods available to sync time-variant LES solutions to those experienced by fish in their natural environment [44]. As a result, our approach used spatial and temporal averaging to account for the inherent uncertainty between linking observed movements in the field to the simulated environment.…”
Section: Hydraulic Cues Of Launch Anglementioning
confidence: 99%